The Effectiveness of Family-Based Dash Education on Older People's Blood Pressure at the Public Health Center of Kutalimbaru - Simorangkir, Lindawati; Ginting, Agustaria; Karo, Mestiana Br; Saragih, Ice Septriani; Ginting, Amnita Anda Yanti Br; Saragih, Helinida; Siringo-ringo, Magda; Ginting, Nasipta (Society, 2022)
Hypertension cases continue to increase worldwide and are the biggest cause of death. In Medan, North Sumatra, the number of hypertensive patients is 7,174 people, and the cause of death is the 4th cause of death. The study aimed to formulate the effectiveness of family-based Dash education on elderly blood pressure at the Kutalimbaru Health Center. This research is a Quasi-Experimental design with one group pretest and posttest design. The population is hypertensive clients at the Kutalimbaru Health Center with a sample of 31 respondents, taken through a purposive sampling technique with the criteria of elderly hypertensive 2-4 years, blood pressure > 140/90 mmHg, age 55 years to 65 years, living with family, receiving medication the same antihypertensive and willing to be a respondent. The instrument used was a sphygmomanometer, a 24-hour Recall observation sheet, and a booklet—analysis with a Wilcoxon sign rank test. Research shows the average systolic blood pressure before 155.16 mmHg after 147.74 mmHg. The average diastolic blood pressure before 85.81 mmHg after 82.26 mmHg. The results of statistical tests showed an effect of family-based education on the blood pressure of older people at the Kutalimbaru Health Center (p = 0.000). The conclusion of family-based education is effective in reducing blood pressure in older people. Suggestions for families are expected to control eating patterns routinely and for older people to have their blood pressure checked regularly at the public health center.